Effect of long-term occupational exposure to extremely low-frequency electromagnetic fields on proinflammatory cytokine and hematological parameters - Hosseinabadi, Majid Bagheri; Khanjani, Narges; Samaei, Seyed Ehsan; Nazarkhani, Fereshteh (International journal of radiation biology, 2019)
Purpose: The present study aimed to investigate the effect of extremely low-frequency electromagnetic fields (ELF-EMFs) on proinflammatory cytokines and hematological parameters, among the employees of a power plant, which are one of the most important occupational groups exposed to ELF-EMFs extensively. Materials and methods: The studied population included 112 employees of a power plant as the exposed group and 138 unexposed employees who were enrolled based on inclusion and exclusion criteria. The magnetic flux density and the strength of the electric field were determined by spot measurements and according to the IEEE C95.3.1 standard. Proinflammatory cytokines including serum interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α); and hematologic parameters of all subjects were measured. Results: The mean level of IL-1β and IL-6, white blood cell count (WBC) and red blood cell count (RBC), lymphocyte percentage (Lym%), mean corpuscular volume (MCV), platelet count (PLT) and procalcitonin (PCT) were significantly more in the exposed group, than the unexposed group. The mean serum levels of IL-6, IL-1β and some of the hematological parameters including WBC, lymphocyte, RBC and hematocrit were higher in technicians which had the highest level of exposure to magnetic fields compared to other groups and these relations were linear. Conclusions: Long-term exposure to ELF-EMFs probably affects immune responses, by stimulating the production of proinflammatory cytokines, and increasing some hematological parameters.